A candidate regulatory variant at the TREM gene cluster associates with decreased Alzheimer's disease risk and increased TREML1 and TREM2 brain gene expression - Carrasquillo, Minerva M; Allen, Mariet; Burgess, Jeremy D; Wang, Xue; Strickland, Samantha L; Aryal, Shivani; Siuda, Joanna; Kachadoorian, Michaela L; Medway, Christopher; Younkin, Curtis S; Nair, Asha; Wang, Chen; et al. (Alzheimer's & dementia, 2017)
Abstract Introduction We hypothesized that common Alzheimer's disease (AD)-associated variants within the triggering receptor expressed on myeloid ( TREM ) gene cluster influence disease through gene expression. Methods Expression microarrays on temporal cortex and cerebellum from ∼400 neuropathologically diagnosed subjects and two independent RNAseq replication cohorts were used for expression quantitative trait locus analysis. Results A variant within a DNase hypersensitive site 5′ of TREM2 , rs9357347-C, associates with reduced AD risk and increased TREML1 and TREM2 levels (uncorrected P  = 6.3 × 10−3 and 4.6 × 10−2 , respectively). Meta-analysis on expression quantitative trait locus results from three independent data sets ( n  = 1006) confirmed these associations (uncorrected P  = 3.4 × 10−2 and 3.5 × 10−3 , Bonferroni-corrected P  = 6.7 × 10−2 and 7.1 × 10−3 , respectively). Discussion Our findings point to rs9357347 as a functional regulatory variant that contributes to a protective effect observed at the TREM locus in the International Genomics of Alzheimer's Project genome-wide association study meta-analysis and suggest concomitant increase in TREML1 and TREM2 brain levels as a potential mechanism for protection from AD.